Estudo da estrutura eletrônica de compostos mesoiônicos - Anjos, Italo Curvelo dos (2011)
Mesoionic compounds are a class of molecules which have attracted the interest of scientific community since the late nineteenth century. Their unique structure has proved to be a challenge for researchers who intended to satisfactorily describe and define it. Those compounds are five-membered heterocyclic rings which possess a delocalized  structure clearly separated in two regions: one with a positive charge and the other with a negative one. In this work the electronic structures of three different mesoionic rings (labeled NOO, NSS and NNCS) were investigated. Several structures were build for each ring using different combinations of substituents. Ground state geometries of 54 structures were fully optimized through DFT calculations using M06-2X functional and a cc-pVTZ basis set. NBO calculations were also performed to obtain further electronic structure data. In addition, four aromatic indexes were calculated for each molecule and a multivariate analysis was carried out using the calculated variables. Results have shown that NOO mesoionic rings which had F atom as an electron-attractor substituent have experienced a bond breaking during the geometry optimization process, therefore, leading to acyclic structures. Also, results pointed out that the calculated Kohn-Sham frontier orbitals were delocalized throughout the structure which doesn t agree with the expected shapes of those orbitals by recent mesoionic definition. In addition, principal components analysis have grouped compounds with similar properties, even joining some molecules from different rings and separating some from similar rings. Analysis pointed out that the substituent groups play a role as important as the ring structure itself on the electronic structure of those compounds. Also, results showed that recent mesoionic definition is not general enough and it can still be improved.